The Act of Incorporation, and the Ordinances and Regulations of the Town of Marietta, Washington County, Ohio 17-18, An Ordinance Preventing the Wanton Use of Firearms, & c., §§ 1-2 (1837) - (:unkn) unknown (My University, 1823)
Prohibited the discharge or explosion of any gun powder within the town limits. Violators fined not less than one but no more than five dollars on the first offense. Following offenses fined at not less then five but no more than ten dollars with all costs.
Keywords: DISCHARGE